LAPISAN SOSIAL MASYARAKAT PERKOTAAN - Rosaliza, Mita (Universitas Lancang Kuning, 2017)
Admitted or denied, the gap in life which leads to the strata in society can be found in any society. The social strata and its consequence is the phenomenon of urban society which is universal, including Bengkalis society. It can easily be seen in the daily life of its people. Each person can place him/herself and be placed by others in certain social strata. Social stratification is one of the elements of social system analysis. Social stratification pattern develops and is realized in various forms influenced by complexity of a society. In this analysis, the data collected based on Rogers’ (1960) social stratification measurement method, i.e objective and subjective measurement. Different criteria used may result on different strata formed which can be seen on respondents’ frequency level on each social strata. Objective criteria consists of the measurements on education, income, power, prestige, type of house, number of children, resident-owned status. Based on objective criteria, by using combined index, from 65 chosen respondents, there are 30 respondents or 46.15% respondents placed in high class and 35 respondents or 53.85% are placed in low class. Respondents who subjectively identify themselves on high class are 12 people or 40 % and on low class are 18 respondents from 30 highclass respondents or about 60%. Those data conclude that social stratification in Bengkalis society is a heterogeneous urban society. The form of social stratification is caused by economic factor, because this factor exactly differentiates people from different kinds of jobs.